A physiologically based toxicokinetic (PBTK) model for moderately hydrophobic organic chemicals in the European eel(Anguilla anguilla) - Brinkmann, Markus; Freese, Marko; Pohlmann, Jan-Dag; Kammann, Ulrike; Preuss, Thomas G.; Buchinger, Sebastian; Reifferscheid, Georg; Beiermeister, Anne; Hanel, Reinhold; Hollert, Henner (Science of The Total Environment, 2015)
The European eel (Anguilla anguilla) is a facultatively catadromous fish species with a complex life cycle. Its current population status is alarming: recruitment has decreased drastically since the 1980s and its stock is still considered to be outside safe biological limits. Although there is no consensus on the reasons for this situation, it is currently thought to have resulted from a combination of different stressors, including anthropogenic contaminants. To deepen our understanding of the processes leading to the accumulation of lipophilic organic contaminants in yellow eels (i.e. the feeding, continental growth stage), we developed a physiologically based toxicokinetic model using our own data and values from the literature. Such models can predict the uptake and distribution of water-borne organic chemicals in the whole fish and in different tissues at any time during exposure. The predictive power of the model was tested against experimental data for six chemicals with noctanol- water partitioning coefficient (log Kow) values ranging from 2.13–4.29. Model performance was excellent, with a root mean squared error of 0.28 log units. This model has the potential to help identify suitable habitats for restocking under eel management plans.